1995
DOI: 10.1159/000188518
|View full text |Cite
|
Sign up to set email alerts
|

Liposoluble Vitamins E and A in Human Renal Cortex and Renal Cell Carcinomas

Abstract: Vitamin E was quantified in renal cell carcinomas (RCC) and in ‘intact’ renal cortex, obtained from 31 patients subjected either to unilateral nephrectomy or to partial resection of the only kidney. Histologically, 14 tumors consisted predominantly of clear cells (group 1) and 17 of other cell types (group 2). In both groups, a significant increase in vitamin E concentration, as compared to the ‘intact’ cortex, was observed: 167.8 ± 27.9 and 68.2 ± 15.2 μg/g wet tissue weight (mean ± SEM) for groups 1 and 2, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…To the best of knowledge, our study is the first one that discovered the upregulation of vitamin E metabolism in bladder caners, which may be caused by inflammation secondary to tumors. Concerning the renal cell carcinoma, Catchpole et al observed that an increased level of α-tocopherol in RCC tumor tissues compared with the normal renal cortex tissue, consistent with the findings of Nikiforova etc 26,33 . Besides, analysing the 66 invasive ovarian carcinomas and 9 borderline tumor tissues by gas chromatography/time-of-flight mass spectrometry, Denkert etc.…”
Section: Discussionsupporting
confidence: 64%
“…To the best of knowledge, our study is the first one that discovered the upregulation of vitamin E metabolism in bladder caners, which may be caused by inflammation secondary to tumors. Concerning the renal cell carcinoma, Catchpole et al observed that an increased level of α-tocopherol in RCC tumor tissues compared with the normal renal cortex tissue, consistent with the findings of Nikiforova etc 26,33 . Besides, analysing the 66 invasive ovarian carcinomas and 9 borderline tumor tissues by gas chromatography/time-of-flight mass spectrometry, Denkert etc.…”
Section: Discussionsupporting
confidence: 64%
“…To the best of knowledge, our study is the first one that discovered the upregulation of vitamin E metabolism in bladder caners, which may be caused by inflammation secondary to tumors. Concerning the renal cell carcinoma, Catchpole et al observed that an increased level of α-tocopherol in RCC tumor tissues compared with the normal renal cortex tissue, consistent with the findings of Nikiforova etc 26,33 . Besides, analysing the 66 invasive ovarian carcinomas and 9 borderline tumor tissues by gas chromatography/time-offlight mass spectrometry, Denkert etc.…”
Section: Discussionsupporting
confidence: 64%
“…Another remarkable finding was the profound up-regulation of α-tocopherol concentration in RCC and despite previous allusions to such an elevated vitamin E concentration [ 29 , 30 ] this finding has as yet not received particular attention. Among all metabolites investigated in our study, α-tocopherol emerged as the most important classifier of normal versus tumorous tissue and therefore underlines the putative importance of vitamin E in RCC biology.…”
Section: Discussionmentioning
confidence: 99%